PENGARUH SUHU, WAKTU, DAN KADAR AIR BAHAN BAKU TERHADAP PIROLISIS SERBUK PELEPAH KELAPA SAWIT - Seri Maulina; Feni Sari Putri (Jurnal Teknik Kimia USU, 2017)
Palm plantation produce waste in form of palm midribs in large number. One of the way to handle and increase the value of palm midrib waste is by pyrolysis. The particle size of raw material that used in this study was 23 – 50 mesh. The reduction of raw material size can increase the heating rate of pyrolysis. This study aimed to analyze the effect of temperature, time, and water content of raw material on the yield and pH of liquid smoke. Pyrolysis of palm midrib powder was processed at 150 oC, 200 oC, and 250 oC with various time was 30 minutes, 60 minutes, and 90 minutes. The study found that the yield of liquid smoke tend to increase with rising pyrolysis temperature and time until the condition when un-condensable gas was produced more so that the increase of pyrolysis temperature and time will further decrease the yield. The highest yield of liquid smoke obtained at 250 oC for 30 minutes, is 20,69%. The best pH of liquid smoke obtained at pyrolysis temperature 250 oC for 90 minutes, is 2,6.